FOOD SAFETY RISK ANALYSIS IN MSME PRODUCT SUPPLY CHAIN FROM SCOR, SIX SIGMA AND HACCP INTEGRATION: ANALISIS RISIKO KEAMANAN PANGAN PADA RANTAI PASOK PRODUK UMKM DARI INTEGRASI SCOR, SIX SI - Muflihatin Nafisah, Nailatul; Catur Wahyuni, Hana (Procedia of Engineering and Life Science, 2024)
MSME baster is a business that is engaged in food, especially meatballs. This MSME baster needs to regulate foodprocessing which aims to avoid chemical microbial contamination and others. Starting from raw materials,processing to consumption by consumers, attention is also given to maintaining product safety. The method used indesigning the layout of production facilities at MSME Baster is the integration of Scor, six sigma and Haccp. TheScore method was chosen because it performs and decomposes the process, can measure the supply chain objectivelybased on existing data and can identify improvements that need to be made to create competitive advantage, the SixSigma method to identify problems in the production process and describe the shortcomings in terms of time, money,customers and opportunities, Haccp can reduce the level of risk to morbidity and mortality associated with theconsumption of unsafe food. From the results in the process of making meatballs, there are 3 types that have beendescribed at the determining stage, namely rotten material, material contaminated with fungi, material contaminatedwith the Pareto diagram, it is known that 39% can cause harm to food is control that comes from the upper limit(UCL) of 0.06271 (LCL) of 0.038 with P (average proportion) of 0.07348363, which means that what happened to thecompany the average proportion was 0.07 or 7%